Concepts and clinical aspects of active implants for the treatment of bone fractures. (1st July 2022) - Ganse, Bergita; Orth, Marcel; Roland, Michael; Diebels, Stefan; Motzki, Paul; Seelecke, Stefan; Kirsch, Susanne-Marie; Welsch, Felix; Andres, Annchristin; Wickert, Kerstin; Braun, Benedikt J; Pohlemann, Tim
Abstract: Nonunion is a complication of long bone fractures that leads to disability, morbidity and high costs. Early detection is difficult and treatment through external stimulation and revision surgery is often a lengthy process. Therefore, alternative diagnostic and therapeutic options are currently being explored, including the use of external and internal sensors. Apart from monitoring fracture stiffness and displacement directly at the fracture site, it would be desirable if an implant could also vary its stiffness and apply an intervention to promote healing, if needed. This could be achieved either by a predetermined protocol, by remote control, or even by processing data and triggering the intervention itself (self-regulated 'intelligent' or 'smart' implant). So-called active or smart materials like shape memory alloys (SMA) have opened up opportunities to build active implants. For example, implants could stimulate fracture healing by active shortening and lengthening via SMA actuator wires; by emitting pulses, waves, or electromagnetic fields. However, it remains undefined which modes of application, forces, frequencies, force directions, time durations and periods, or other stimuli such implants should ideally deliver for the best result. The present paper reviews the literature on active implants and interventions for nonunion, discusses possible mechanisms of active implants and points out where further research and development are needed to build an active implant that applies the most ideal intervention. Statement of significance: Early detection of delays during fracture healing and timely intervention are difficult due to limitations of the current diagnostic strategies. New diagnostic options are under evaluation, including the use of external and internal sensors. In addition, it would be desirable if an implant could actively facilitate healing ('Intelligent' or 'smart' implant). Implants could stimulate fracture healing via active shortening and lengthening; by emitting pulses, waves, or electromagnetic fields. No such implants exist to date, but new composite materials and alloys have opened up opportunities to build such active implants, and several groups across the globe are currently working on their development. The present paper is the first review on this topic to date. Grapgical abstract: Image, graphical abstract